Qui gardera nos enfants? Les nounous et le mères: une enquête de Caroline Ibos (Balthazar, 2021)
Although Caroline Ibos' book was published in France in 2012, it is still relevant today.  Starting from the ethnography of the asymmetrical relationship between white mothers and black nounous, the text reflects on the problem of the globalization of the care chain in contemporary capitalism. The author discusses urgent topics for our country, where care workers are subjected to precarious and underpaid work regimes, imbricated with the “norm of love”.